The impact of visuospatial perception on distance judgment and depth perception in an Augmented Reality environment in patients after stroke: an exploratory study - Höhler, Chiara; Rasamoel, Nils David; Rohrbach, Nina; Hansen, John Paulin; Jahn, Klaus; Hermsdörfer, Joachim; Krewer, Carmen (Journal of neuroengineering and rehabilitation, 2021)
Augmented Reality (AR)-based interventions are applied in neurorehabilitation with increasing frequency. Depth perception is required for the intended interaction within AR environments. Until now, however, it is unclear whether patients after stroke with impaired visuospatial perception (VSP) are able to perceive depth in the AR environment. Different aspects of VSP (stereovision and spatial localization/visuoconstruction) were assessed in 20 patients after stroke (mean age: 64 ± 14 years) and 20 healthy subjects (HS, mean age: 28 ± 8 years) using clinical tests. The group of HS was recruited to assess the validity of the developed AR tasks in testing stereovision. To measure perception of holographic objects, three distance judgment tasks and one three-dimensionality task were designed. The effect of impaired stereovision on performance in each AR task was analyzed. AR task performance was modeled by aspects of VSP using separate regression analyses for HS and for patients. In HS, stereovision had a significant effect on the performance in all AR distance judgment tasks (p = 0.021, p = 0.002, p = 0.046) and in the three-dimensionality task (p = 0.003). Individual quality of stereovision significantly predicted the accuracy in each distance judgment task and was highly related to the ability to perceive holograms as three-dimensional (p = 0.001). In stroke-survivors, impaired stereovision had a specific deterioration effect on only one distance judgment task (p = 0.042), whereas the three-dimensionality task was unaffected (p = 0.317). Regression analyses confirmed a lacking impact of patients' quality of stereovision on AR task performance, while spatial localization/visuoconstruction significantly prognosticated the accuracy in distance estimation of geometric objects in two AR tasks. Impairments in VSP reduce the ability to estimate distance and to perceive three-dimensionality in an AR environment. While stereovision is key for task performance in HS, spatial localization/visuoconstruction is predominant in patients. Since impairments in VSP are present after stroke, these findings might be crucial when AR is applied for neurorehabilitative treatment. In order to maximize the therapy outcome, the design of AR games should be adapted to patients' impaired VSP.  Trial registration: The trial was not registered, as it was an observational study.